Fabricating micromilling tool using wire electrodischarge grinding and focused ion beam sputtering - Ali, Mohammad Yeakub; Ong, A. S. (Springer, 2006)
This paper discusses the microfabrication of micromilling tools using wire electrodischarge grinding (WEDG) and focused ion beam (FIB) sputtering. The tool blank of tungsten carbide was produced by WEDG and the cutting edges were formed by FIB sputtering. Using these two complementary processes micromilling tools were fabricated with submicrometer accuracy and nanometric levelled surface finish. The fabricated microtools were used to mill microchannels on polymer. The fabricated microtool and microchannels were inspected using an optical surface profiler, atomic force microscope (AFM) and scanning electron microscope (SEM). The length of the microchannels ranges from 0.5 mm to 2 mm. The maximum trench depth was 5μm. The widths of the channels were about 10–20% larger than the tool diameter when milling without and with lubrication, respectively. An average surface finish of 80 nm was achieved.